Dipeptidyl Peptidase-4 Is a Pro-Recovery Mediator During Acute Hepatotoxic Damage and Mirrors Severe Shifts in Kupffer Cells - Duarte, Nádia (2018)
This deposit is composed by the main article plus the supplementary materials of the publication.